The water consumption of energy production: an international comparison - Spang, E S; Moomaw, W R; Gallagher, K S; Kirshen, P H; Marks, D H (Environmental research letters, 2014)
Producing energy resources requires significant quantities of fresh water. As an energy sector changes or expands, the mix of technologies deployed to produce fuels and electricity determines the associated burden on regional water resources. Many reports have identified the water consumption of various energy production technologies. This paper synthesizes and expands upon this previous work by exploring the geographic distribution of water use by national energy portfolios. By defining and calculating an indicator to compare the water consumption of energy production for over 150 countries, we estimate that approximately 52 billion cubic meters of fresh water is consumed annually for global energy production. Further, in consolidating the data, it became clear that both the quality of the data and global reporting standards should be improved to track this important variable at the global scale. By introducing a consistent indicator to empirically assess coupled water-energy systems, it is hoped that this research will provide greater visibility into the magnitude of water use for energy production at the national and global scales.